Effect of Audio-Visual Aids on Students’ Academic Achievement in Mechanical Engineering Craft Practice in Technical Colleges in Rivers State - Okwelle P. Chijioke; Orikoha Ekwueme (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study investigated the effect of audio-visual aids on students’ academic achievement in mechanical engineering craft practice in technical colleges in Rivers State. Two research questions were posed and two null hypotheses were tested in the study. Quasi-experimental design was adopted for the study. Purposive sampling technique was used to draw the three technical colleges offering Mechanical Engineering Craft Practice out of the four technical colleges in the state. A multi-choice test instrument tagged “Mechanical Engineering Craft Practice Achievement Test” was used for data collection. Research questions were answered using mean. Analysis of covariance (ANCOVA) statistics was used to test hypotheses at 0.05 level of significance. The study recommended that teachers of mechanical craft practice and other technical disciplines should vigorously adopt the use of audio-visual aids amongst other active instructional aids in the delivery of their day to day lessons.